Tinjauan ’Urf terhadap Tradisi Arakan Pengantin dalam Pernikahan: Studi Kasus Desa Morocalan, Glagah, Lamongan - Rahmawati, Richah; Aminah, Siti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2024)
‘Urf refers to an action or expression that is repeatedly performed, regarded as good, and does not violate sharia principles. Marriage is the bond between a man and a woman, both physically and emotionally, aimed at building a family characterized by sakinah (tranquility), mawaddah (love), and rahmah (compassion). One of the traditions in marriage is the bridal procession, which involves escorting the bride and groom on foot after the wedding ceremony (akad nikah). This study aims to examine the implementation process of the bridal procession and its analysis through the perspective of urf. The research method used is qualitative, employing field research. The findings reveal that the bridal procession in wedding ceremonies in Morocalan Village, Glagah Sub-district, Lamongan Regency, is performed by the groom. The groom is escorted on foot from one end of the village to the bride's house. This tradition serves as an expression of gratitude for the end of bachelorhood and as a way to celebrate the wedding, which is considered a once-in-a-lifetime event. From the perspective of Islamic law and urf, the bridal procession is deemed a legitimate tradition, as it does not contravene Indonesia’s positive law or Islamic principles. Furthermore, this tradition carries positive values for both the bride and groom and their families